Functional groups of sialic acids involved in binding to siglecs (sialoadhesins) deduced from interactions with synthetic analogues - Kelm, Sørge; Brossmer, Reinhard; Isecke, Rainer; Groß, Hans Jürgen; Strenge, Karen; Schauer, Roland (EJB, 1998)
The siglecs, formerly called sialoadhesins, are a family of I-type lectins binding to sialic acids on the cell surface. Five members of this family have been identified : sialoadhesin, myelin-associated glycoprotein (MAG), Schwann cell myelin protein (SMP), CD22 and CD33. We have investigated the relevance of substituents at position C-9 and in the N-acetyl group of N-acetylneuraminic acid, using a series of synthetic sialic-acid analogues either on resialylated human erythrocytes or as free α-glycosides in hapten inhibition. All five siglecs require the hydroxy group at C-9 for binding, suggesting hydrogen bonding of this substituent with the binding site. Remarkable differences were found among the proteins in their specificity for modifications of the N-acetyl group. Whereas sialoadhesin, MAG and SMP do not tolerate a hydroxy group as in N-glycolylneuraminic acid, they bind to halogenated acetyl residues. In the case of MAG, N-fluoroacetylneuraminic acid is bound about 17-fold better than N-acetylneuraminic acid. In contrast, human and murine CD22 both show good affinity for N-glycolylneuraminic acid, but only human CD22 bound the halogenated compounds. In conclusion, our data indicate that interactions of the hydroxy group at position 9 and the N-acyl substituent contribute significantly to the binding strength.